2015
DOI: 10.1371/journal.pone.0138203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Creosote Bush-Derived NDGA on Expression of Genes Involved in Lipid Metabolism in Liver of High-Fructose Fed Rats: Relevance to NDGA Amelioration of Hypertriglyceridemia and Hepatic Steatosis

Abstract: Nordihydroguaiaretic acid (NDGA), the main metabolite of Creosote bush, has been shown to have profound effects on the core components of the metabolic syndrome (MetS), lowering blood glucose, free fatty acids (FFA) and triglyceride (TG) levels in several models of dyslipidemia, as well as improving body weight (obesity), insulin resistance, diabetes and hypertension, and ameliorating hepatic steatosis. In the present study, a high-fructose diet (HFrD) fed rat model of hypertriglyceridemia was employed to furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 65 publications
(79 reference statements)
3
19
0
Order By: Relevance
“…A short-term (4 days) NDGA treatment attenuated hyperinsulinemia, and fasting plasma glucose and NEFA levels. Analysis of HOMA-IR further confirmed that NDGA treatment ameliorated insulin resistance induced by feeding a high-fructose diet (Zhang et al, 2015). In contrast, we reported previously that NDGA treatment improved both glucose intolerance and insulin sensitivity in ob/ob mice (Zhang et al, 2013).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…A short-term (4 days) NDGA treatment attenuated hyperinsulinemia, and fasting plasma glucose and NEFA levels. Analysis of HOMA-IR further confirmed that NDGA treatment ameliorated insulin resistance induced by feeding a high-fructose diet (Zhang et al, 2015). In contrast, we reported previously that NDGA treatment improved both glucose intolerance and insulin sensitivity in ob/ob mice (Zhang et al, 2013).…”
Section: Discussionsupporting
confidence: 61%
“…However, feeding mice ALIOS diet supplemented with NDGA improved insulin sensitivity, but mice (Zhang et al, 2015). A short-term (4 days) NDGA treatment attenuated hyperinsulinemia, and fasting plasma glucose and NEFA levels.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…No validated therapies for NAFLD currently exist (Barb et al ., ). Previous studies from this laboratory have shown that nordihydroguaiaretic acid (NDGA , also called masoprocol), the active ingredient of the folk medicinal plant, Creosote bush (Arteaga et al ., ), exerts profound effects on several components of the metabolic syndrome, including lowering blood glucose, FFAs, and TG levels and attenuating elevated BP in several rodent models of dyslipidaemia, insulin resistance and hypertension (Gowri et al ., ,b, ; Scribner et al ., ; Zhang et al ., , , ). Previously, we provided evidence that the beneficial actions of NDGA on dyslipidaemia and hepatic steatosis in ob/ob mice are exerted primarily through enhanced fatty acid oxidation via PPARα ‐dependent pathways (Zhang et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we provided evidence that the beneficial actions of NDGA on dyslipidaemia and hepatic steatosis in ob/ob mice are exerted primarily through enhanced fatty acid oxidation via PPARα ‐dependent pathways (Zhang et al ., ). More recently, we reported that both acute and chronic treatment of high‐fructose diet (HFrD) fed dyslipidaemic rats ameliorates hypertriglyceridaemia and hepatic steatosis primarily by promoting increased channelling of fatty acids towards their β‐oxidation and interfering with lipogenesis (Zhang et al ., , ).…”
Section: Introductionmentioning
confidence: 99%